Collocational Characteristics of the Thanking Speech Formula “Thank You” - A.I. Bochkarev (Ученые записки Казанского университета: Серия Гуманитарные науки, 2016)
The paper is devoted to the issues of combinatory syntax, and more particularly to studying the collocational characteristics of the thanking speech formula “thank you”. The relevance of the research consists in the fact that there still have been no special studies of the combinatory characteristics of syntactic units. A review of the available theoretical material underlying combinatorial syntax has been made. The author has distinguished two main groups of functions which the analyzed thanking formula can perform. The first group includes the cases when thanking is the main function of the thanking speech formula “thank you”. Cases in which expression of thanking is the secondary function of the corresponding speech formula belong to the second group. The collocational characteristics of the thanking speech formula “thank you” have been analyzed, i.e., combinations of the speech formula in all its meanings with other utterances. Four general combinatory groups where thanking is the main function of the speech formula “thank you” have been found out: 1) [eliciting X] – [providing X] – [thank you]; 2) [offering X] – [thank you]; 3) [introducing communicant] – [thank you]; 4) [greeting + thank you]. Based on the analysis of the practical material, two combinatory groups where thanking is the secondary function of the speech formula “thank you” have been distinguished: 1) finishing speech situation + thanking; 2) appealing to the God + thanking. The obtained results show the productivity of the approach to the study of language units functioning from the perspective of combinatorial syntax, which gives hope for further fruitful study of the combinatory characteristics of the speech formulas of expressives and declarations.